Treatment of mucus retention phenomena in children by the micro-marsupialization technique: case reports - Delbem, Alberto Carlos Botazzo [UNESP]; Cunha, Robson Frederico [UNESP]; De Mello Vieira, Ana Elisa; Ribeiro, Luciana Liarte Gasparini (My University, 2000)
The purpose of the present study was to emphasize the technique of micro-marsupialization as an alternative for the treatment of mucus retention phenomena. Out of 41 patients, 14 were selected for treatment by the micro-marsupialization technique on the basis of clinical criteria. Patient age ranged from 5-9 years. The technique was performed as follows: the area was disinfected with 0.1% iodine; a topical anesthetic was applied to cover the entire lesion for approximately 3 min; a 4.0 silk suture was passed through the internal part of the lesion along its widest diameter; and a surgical knot was made. Of the original 14 patients treated by the micro-marsupialization technique, 12 presented full regression one week after treatment. Recurrence occurred in two cases. It was possible to conclude that the micro-marsupialization technique is an alternative to be considered, especially in pediatric dentistry.
Keywords: case report; child; differential diagnosis; female; human; male; methodology; microsurgery; mouth disease; mouth mucosa; mucocele; oral surgery; pathology; preschool child; salivary gland tumor; Child; Child, Preschool; Diagnosis, Differential; Female; Humans; Male; Microsurgery; Mouth Diseases; Mouth Mucosa; Mucocele; Oral Surgical Procedures; Salivary Gland Neoplasms